THC-induced behavioral stereotypy in zebrafish as a model of psychosis-like behavior - Amelia Dahlén (Nature Portfolio, 2021)
Abstract High doses of the Cannabis constituent Δ9-tetrahydrocannabinol (THC) increase the risk of psychosis in humans. Highly accessible animal models are needed to address underlying mechanisms. Using zebrafish with a conserved endocannabinoid system, this study investigates the acute effects of THC on adult zebrafish behavior and the mechanisms involved. A concentration-dependent THC-induced behavioral stereotypy akin to THC’s effect in rats and the psychotropics phencyclidine and ketamine in zebrafish was established. Distinctive circular swimming during THC-exposure was measured using a novel analytical method that we developed, which detected an elevated Repetition Index (RI) compared to vehicle controls. This was reduced upon co-administration of N-methyl-D-aspartate (NMDA) receptor agonist NMDA, suggesting that THC exerts its effects via biochemical or neurobiological mechanisms associated with NMDA receptor antagonism. Co-treatment of γ‐aminobutyric acid receptor antagonist pentylenetetrazol also showed signs of reducing the RI. Since THC-induced repetitive behavior remained in co-administrations with cannabinoid receptor 1 inverse agonist AM251, the phenotype may be cannabinoid receptor 1-independent. Conversely, the inverse cannabinoid receptor 2 agonist AM630 significantly reduced THC-induced behavioral stereotypy, indicating cannabinoid receptor 2 as a possible mediator. A significant reduction of the THC-RI was also observed by the antipsychotic sulpiride. Together, these findings highlight this model’s potential for elucidating the mechanistic relationship between Cannabis and psychosis.